Electrochemical Biosensor Based on Laser-Induced Graphene for COVID-19 Diagnosing: Rapid and Low-Cost Detection of SARS-CoV-2 Biomarker Antibodies - Marcely Echeverria Oliveira; Bruno Vasconcellos Lopes; Jéssica Helisa Hautrive Rossato; Guilherme Kurz Maron; Betty Braga Gallo; Andrei Borges La Rosa; Raphael Dorneles Caldeira Balboni; Mariliana Luiza Ferreira Alves; Marcos Roberto Alves Ferreira; Luciano da Silva Pinto; Fabricio Rochedo Conceição; Evandro Piva; et al. (Surfaces, 2022)
The severe acute respiratory syndrome originated by the new coronavirus (SARS-CoV-2) that emerged in late 2019, known to be a highly transmissible and pathogenic disease, has caused the COVID-19 global pandemic outbreak. Thus, diagnostic devices that help epidemiological public safety measures to reduce undetected cases and isolation of infected patients, in addition to significantly help to control the population’s immune response to vaccine, are required. To address the negative issues of clinical research, we developed a Diagnostic on a Chip platform based on a disposable electrochemical biosensor containing laser-induced graphene and a protein (SARS-CoV-2 specific antigen) for the detection of SARS-CoV-2 antibodies. The biosensors were produced via direct laser writing using a CO2 infrared laser cutting machine on commercial polyimide sheets. The presence of specific antibodies reacting with the protein and the K3[Fe(CN)6] redox indicator produced characteristic and concentration-dependent electrochemical signals, with mean current values of 9.6757 and 8.1812 µA for reactive and non-reactive samples, respectively, proving the effectiveness of testing in clinical samples of serum from patients. Thus, the platform is being expanded to be measured in a portable microcontrolled potentiostat to be applied as a fast and reliable monitoring and mapping tool, aiming to assess the vaccinal immune response of the population.